Endocytosis in rat cultured astrocytes is inhibited by unconjugated bilirubin - Silva, RFM (2015)
Excessive hyperbilirubinemia can cause irreversible neurological damage in the neonatal period. However, the complete understanding of the pathogenesis of unconjugated bilirubin (UCB) encephalopathy remains a matter of debate. This study investigates whet